Development of neurotransmitter systems and their reflections on psychopathology [Nörotransmitter sistemlerinin gelişimi ve psikopatolojiye yansimalari] - (:unkn) unknown (My University, 2009)
During early stages of postnatal period brain morphology consists of undifferentiated, large, nonproportional topographic configurations. Later, these initial structures undergo adaptive changes by way of sensory and motor experiences. Molecular maturation of the brain takes place via two different processes defined as experience-dependent and experience-expectant organization. The major neurotransmitter systems of the brain, namely acethylcholine, glutamate, GABA, serotonin, dopamine, and norepinephrine undergo developmental changes, which occur in parallel with developmental topographic changes of the brain during postnatal period. On the other hand, any unexpected, changes in these systems are found to be related to different psychopathologies. In this review developmental changes in neurotransmitter systems that are expected to occur during postnatal period will be reviewed. Then the findings related to the neurotransmitter systems which are thought to be underlying causes for childhood and teenage psychopathologies will be discussed.
Keywords: Neurotransmitter; Postnatal development; Psychopathology